Rancang Bangun Sistem Keamanan Dan Pengendali Jarak Jauh Sepeda Motor Menggunakan Android Berbasis Nodemcu ESP32 dan GPS - Romadlon Ardliyansyah, Moh Soleh; Bachri, Affan (Jurnal FORTECH, 2022)
Technological developments have penetrated various fields, including motor vehicle safety. The manufacturer's standard locking system is deemed insufficient to protect motorized vehicles from theft. A combination of software and hardware is required to create an additional security system. The purpose of this research is to design and build a motorcycle safety device using IoT-based GPS. The system is designed when a forced vibration occurs in the ignition zone, a warning message is sent via the Blynk application and the horn sounds. To turn on the machine, you can via the widget in the Blynk application, the Contacts button is ON, then press the Machine ON to turn off the machine by pressing the Contacts OFF button in the Blynk application. To detect the location of a smartphone-controlled motorcycle with the Blynk application. The design of this tool uses several components, namely the SW-420 vibration sensor as an engine warning indicator sensor, the Neo6mv2 GPS sensor as a coordinate sensor, using the NodeMCU ESP32 microcontroller to process data and communicate with a WiFi modem and use a relay as a control button to turn on and off the engine, turn on horn. All components require a 5V supply voltage from a 12V motor battery, this voltage is reduced to 5V with the LM2596 module.